Evolution of erythrocytes aggregation: A fractal approach when incubated with Trichinella spiralis and Ascaris lumbricoides - Lupo, Maela (2016)
Fractal geometry has provided a new range of concepts that could explain the non-linear behaviour of seemingly unpredictable natural systems. The aim of this work is to apply nonlinear analysis to study the . in vitro erythrocyte aggregation produced by incubation of human red blood cells (RBCs) with . Ascaris lumbricoides and also . Trichinella spirallis larvae extracts. The approach used was based on calculating the fractal slope (D), through image processing of control and treated RBCs at different incubation times (200 images). The results showed a decrease in the fractal dimension value of . Ascaris lumbricoides treated RBCs (up to 10%) and a constant value of D in the case of . Thichinella spiralis treated RBCs, in contrast to a more disperse value showed in normal controls. This modification in the D might be correlated with the different actions of each parasite over the erythrocyte membrane leading to abnormal RBCs aggregation.